Mengatasi Self-Harm di Kalangan Remaja: Pendekatan Pendidikan Karakter dalam Perspektif Islam - Silna Rahmatika; Syahidin Syahidin (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Self-Harm is an act of conscious self-harm to eliminate pain and disturbing thoughts in one's personality. Nowadays, Self-Harm Behavior tends to occur in teenagers in Indonesia with various factors and consequences. Various approaches also need to be taken to overcome this behavior. Islam always teaches the goodness and welfare of its servants. This Self-Harm behavior is classified as an unjust act which results in mental and physical damage to a person. This article discusses how character education based on Islamic values can be an alternative for overcoming self-harm behavior. Thus, Islamic-based character education not only plays a role in moral formation, but also plays a role in the mental well-being of teenagers.